Respect Your Elders: Generativity and Life Satisfaction in Caregiving Grandparents. (April 2023) - Scott, Rachel K.; Nadorff, Danielle K.; Barnett, Melissa; Yancura, Loriena
Erikson's theory of psychosocial development defines generativity as the drive to benefit future generations and leave a legacy. Generativity has been shown to predict life satisfaction, but generative concern and action can be impacted by factors such as perceived respect from younger generations. This study utilized caregiving grandparents aged 40 and older to assess the extent to which perceived respect mediated the relation between generativity and life satisfaction. Perceived respect from a grandchild mediated the relation between generative concern expressed by caregiving grandparents and life satisfaction after controlling for demographic variables that have been shown to influence heterogeneity and overall well-being in caregiving grandparent samples. These findings suggest that the relation between life satisfaction and generativity in grandparents may depend, in part, on perceived respect from grandchildren, intimating that the implications of generativity may be influenced by the perceived appreciation of its recipients.